Overhead distribution lines : design and applications - Slavin, Lawrence M. (Wiley, 2021)
"This book provides expert knowledge to those in the power and communication utility industry in how to design power and communication distribution lines. Information is presented on the physical characteristics of various types of utility poles, overhead supply and communication cables, installation practices, joint-usage issues and safety rules, including national standards and other related documents. It provides critical details on industry software to guide engineers in its effective use. Care is taken to describe the critical requirements to select the proper poles for specific applications. The author includes a final chapter that describes comprehensive examples of the information introduced earlier"--